Effect of Implementing Flipped Classroom Method of Teaching Learning in Biochemistry on Student Learning and Student Perception about Flipped Classroom - AS Shilpasree; Ramyashree Vyas; Vidya S Patil; Srirang P Kulkarni (Indian Journal of Medical Biochemistry)
Aim and background: Due to a drastic increase in the number of students having diverse learning styles and a growing need for modern-world students to use technological approaches for learning, medical teachers are compelled to adopt flexible, blended, and student-centered teaching and learning strategies. Flipped classroom can be regarded as a ‘student-centered approach to teaching and learning’ that emphasizes peer interaction, active learning, and in-depth understanding of topics in a group of students having diverse learning styles. The method allows flexibility in pace with adequate and efficient utilization of digital tools. The present study was conducted to evaluate the effectiveness of flipped class in terms of the academic performance of students and to assess student perception regarding the flipped classroom method of teaching and learning. Materials and methods: One hundred and fifty undergraduate students from Phase 1 MBBS were randomly allocated into two groups. A 2-hour session on cancer genetics was conducted for group I in the traditional manner, and a flipped classroom approach was adopted for group II. Crossover of groups was done for the next session. At the end of each session, student learning was assessed using MCQs, and student perception was recorded in the form of a feedback. Results: A total of 126 students attended session 1, and 121 students attended session 2. During intergroup comparison, median MCQ scores of students attending flipped classroom were significantly higher than the scores of students attending traditional lectures. In paired analysis, students performed better after attending a flipped classroom than a traditional lecture. On feedback analysis, the majority of the students perceived the flipped classroom as a better teaching-learning method compared to the traditional lecture. Conclusion: Flipped classroom can be regarded as an effective alternative to traditional lecture as it enhances student engagement, active learning, and academic performance. Students also consider it an excellent approach, as it addresses the needs of diverse learners.